(3eHGOF EOGQI GdafGOb (B/s - (3Jhajb, eGgQ YHO GdYRjRs ((3YeGf(B: s (3OGQ RgQGf ddfTQ hGdJhRjY(B, s, 1998)
(3deMI JGQjNjI Yf JWhjQ GdafGOb hCeGcf GdEjhGA ,JYQja GdafOb hJbSjeg ef MjK GdedcjI hGdebY hGdNOeGJ,JUfja GdafGOb,OQGSI Gdgjcd GdJfXjej ddafGOb,hUa GdCbSGe GdYGedI aj GdafGOb,GdJfXje GdafObj,GdafGOb GdYGdejI hGdTQcGJ GdafObjI ,GdESJZdGd GdafObj ,GdYhGed GdJj JSGYO Ydi fLGM GdafOb,NOeI GdUha,GdGTQGb hGdEOGQI GdafObjI ,GdfSH hGdGMUGAGJ GdafObjI,OQGSI GdLOhi GdEbJUGOjI ddafGOb , eUWdMGJ afObjIs
(3GdeQGLY U(B.368s
Keywords: (3GdEOGQIs; (3GdSjGMIs; (3GdafGObs